P0412VALUE OF INTERNATIONAL RISK-PREDICTION TOOL IN IGA NEPHROAPTHY : A SINGLE CENTRE STUDY. (6th June 2020) - Arora, Dhawal; Kanigicherla, Durga; Hamilton, Patrick
Abstract: Background and Aims: A new International Risk-Prediction Tool in IgA Nephropathy developed was recently developed to help predict disease progression over a 5-7 year period 1 . We tested use of this Risk-Prediction Calculator in patients diagnosed with IgA Nephropathy to stratify the risk and predict outcomes during follow up. Method: All adult patients (aged ≥18years) with biopsy proven IgA Nephropathy diagnosed between 2011 and 2016 at Manchester University NHS Foundation Trust were included in the study. Exclusion criteria included patients with secondary causes, prior exposure to immunosuppression, or presentation eGFR of less that 15ml/min. Demographic, clinical phenotypic & renal histological characteristics (MEST score) at baseline were used to calculate the individual risk scores. These risk scores were compared with outcomes seen during subsequent follow up. Primary outcome was a composite of first ESRD or reduction in eGFR to below 50% of value at biopsy. Patients were censored at last follow visit for primary outcome or death. Renal outcomes were analysed using Kaplan Meier survival plots of subgroups based on predicted risk (<16 th percentile, 16-50 th percentile, 50-84 th percentile or >84 th percentile). Results: 121 patients were included in the analyses. 45 other patients were excluded based on exclusion criteria. 84 patients (69%) were males, mean age was 42±16 years, eGFR was 63±34ml/min and uPCR was 151±42mg/mmol. Mean follow up was 51.4±28 months. 87% were on RAS inhibition at or within 6 weeks of kidney biopsy diagnosis. During the follow up period 23 patients (19%) developed the primary outcome. Outcomes were significantly worse in patients with higher risk-prediction scores (Fig 1 log rank p<0.01). Conclusion: This single centre study confirms that the International IgA Nephropathy Risk-Prediction Model for kidney outcomes can be a valuable tool for prognostication in Primary IgA Nephropathy in routine clinical practice.